Peran Guru Terhadap Perkembangan Sosial Emosional Anak Di RA Al Fath - Yeni Mulyawani; Muthia Sari; Lira Erwinda; Novita Sari; Nedi Kurnaedi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Social-emotional development is a fundamental aspect of early childhood education, as it shapes children's ability to regulate emotions, interact socially, and develop empathy and responsibility. This study aimed to describe the social-emotional development of Group B children and analyze the role of teachers in supporting their social-emotional development at RA Al Fath. A descriptive qualitative approach was employed. Data were collected through in-depth interviews with classroom and assistant teachers, classroom observations, and documentation, and were analyzed using thematic analysis. The findings reveal that children's social-emotional development falls into three categories: Beginning to Develop, Developing as Expected, and Developing Very Well, with differences in emotional regulation, turn-taking, cooperation, and compliance with classroom rules. The study also found that teachers play significant roles as educators, supervisors, managers, innovators, and motivators by providing positive role models, creating supportive classroom environments, resolving conflicts constructively, implementing play-based learning, and reinforcing positive behavior. The findings imply that strengthening teachers' competencies in social-emotional learning and fostering sustainable collaboration between schools and parents should become integral components of early childhood education programs to promote optimal social-emotional development among young children